Optimization of a multipurpose river basin in anambra state, Nigeria - Ekwueme O. G; Aronu Charles O (Institute of Computer Science (IOCS), 2023)
In this study, the multipurpose objective of development in the Anambra River basin was examined. The study's goals are to determine the net benefits of the various objectives under each purpose currently carried out by the Anambra River Basin, to identify the best way to achieve the goals, and to show, through logical and mathematical reasoning, how money could be allocated to the various goals of a dam project in Anambra State effectively. Economic Efficiency (EE), Regional Economic Redistribution (RER), Social Well-Being (SW), Youth Empowerment (YE), and Environmental Quality Improvement are the objectives taken into account in the study (EQI). The optimization problem in the multi-purpose-objective development of the Anambra State river basin was solved utilizing the multi-start optimization method. The study showed that the basin would achieve enormous financial benefits if it used its N15.0 billion strategic development budget over four years for various purposes as illustrated. The results showed that the following allocation of the five purposes should be optimized simultaneously for an N15.0 billion four-year strategic development fund: EE should receive N0.762 billion, RER should receive N0.594 billion, SW should receive N0.649 billion, YE should receive N0.683 billion, and environmental quality improvement should receive N4.768 billion. It was found that Environmental Quality Improvement was allocated the higher amount while Regional Economic Redistribution was allocated the least amount for the development. The study's findings recommended that the management of the basin stop the practice of allocating funds to various uses at their discretion, which has led to significant oversight and the improper distribution of scarce resources. As a result, every fund distribution must be justified using logic and mathematics. To increase the accuracy of the data, the Anambra State River Basin Development Authorities must intensify record-keeping activities.